Neuroinflammation and Scarring After Spinal Cord Injury: Therapeutic Roles of MSCs on Inflammation and Glial Scar - Pang, Qi-Ming; Chen, Si-Yu; Xu, Qi-Jing; Fu, Sheng-Ping; Yang, Yi-Chun; Zou, Wang-Hui; Zhang, Meng; Liu, Juan; Wan, Wei-Hong; Peng, Jia-Chen; Zhang, Tao (Frontiers in Immunology, 2021)
Transected axons are unable to regenerate after spinal cord injury (SCI). Glial scar is thought to be responsible for this failure. Regulating the formation of glial scar post-SCI may contribute to axonal regrow. Over the past few decades, studies have found that the interaction between immune cells at the damaged site results in a robust and persistent inflammatory response. Current therapy strategies focus primarily on the inhibition of subacute and chronic neuroinflammation after the acute inflammatory response was executed. Growing evidences have documented that mesenchymal stem cells (MSCs) engraftment can be served as a promising cell therapy for SCI. Numerous studies have shown that MSCs transplantation can inhibit the excessive glial scar formation as well as inflammatory response, thereby facilitating the anatomical and functional recovery. Here, we will review the effects of inflammatory response and glial scar formation in spinal cord injury and repair. The role of MSCs in regulating neuroinflammation and glial scar formation after SCI will be reviewed as well.